TEKNOLOGI PROSES PELENGKUNGAN ROTAN SECARA KIMIA UNTUK BAHAN BAKU MEBEL - Arsad, Effendi (Jurnal Riset Industri Hasil Hutan, 2011)
ABSTRACTThe  research was design to know the impact of chemical compound in deflexioning  process of the rattan for furniture material. There are three kinds of rattan  using for this research.  They are manau ( Calamus manna Miq.),  batang  (Daemonorops robusta Warb.)  and suti (Calamus ormatus BI). The chemical compounds that used in this research are  Natrium Hidroksida ( NaOH) and Dimetylsulfoxside ( DMSO). The  result of water content is  12,98%.  and this fulfilled the requirement for the funiture   material which is  14%.  The higher  of the  NaOH and DMSO   concentration used is causing the increasing of rattan density.  The same  effect is shown in the  bending strength ( MOR) and elasticity strength ( MOE), the higher of the chemical compound  concentration  is cause the rattan more easy to deflex.Keywords: rattan,  plastisation,  deflexion  NaOH, DMSO,  funiture